Japan's security policy: A shift in direction under Abe? - Alexandra Sakaki (Stiftung Wissenschaft und Politik (SWP), 2015)
Change is in the air in Japan under the leadership of Shinzo Abe, who in 2012 became Prime Minister again after a first term of office in 2006/2007. In his second term, Abe not only wants to halt Japan's economic decline; he also intends to forestall any further deterioration in the country's geopolitical significance and return Japan to its former strength. With these goals in mind, Abe has initiated a series of security policy reforms, including the first increase in the defense budget in years (in fiscal year 2013); the introduction of a National Security Council and a Security Strategy (December 2013); the relaxation of former arms export restrictions (April 2014); and a reinterpretation of the 'peace clause' of the Constitution (July 2014). In the view of many observers, these developments amount to a radical change in Japan's security policy. A detailed analysis, however, shows that internationally too much importance has been attached to the changes ushered in by Abe. Those who claim to discern seminal changes or even a shift in direction fail to take into account the process of transformation and adjustment that Tokyo has been undergoing since as early as the end of the Cold War. Abe's reforms are the logical consequence and result of the gradual realignment of Japan's security policy, a process long underway. Faced with a complex security environment, the Abe administration is attempting to better protect the country from security risks and influence regional developments to Japan's advantage. The alliance with the US remains the linchpin of Japan's foreign and security policy. In addition, Tokyo has been strengthening its cooperation with other partners, particularly Australia, India and several Southeast Asian countries. (SWP Research Paper)
Keywords: 320